Different Frequency Bands in Various Regions of the Brain Play Different Roles in the Onset and Wake-Sleep Stages of Infantile Spasms - Dong, Yan; Xu, Ruijuan; Zhang, Yaodong; Shi, Yali; Du, Kaixian; Jia, Tianming; Wang, Jun; Wang, Fang (Frontiers in Pediatrics, 2022)
Objective: To identify the characteristic changes and mechanism of some brain networks of electroencephalogram (EEG) in infantilespasms (IS). Methods: Scalp EEGs of IS were prospectively collected in patients with IS [n=8, age = 6.50 (5.25, 8) months, range 4–8 months, 3 males]in the first year of life. Ten minutes of ictal and interictal EEGs were clipped and filtered into different EEG frequency bands. Valuesof each pair of EEG channels were directly compared between ictalwithinterictal onsets,sleep-wake phase to calculate EEG measures of node degree (ND), characteristic path length (CPL), the clustering coefficient (CC), and betweenness centrality (BC). Results:Connectivity and defense capabilities were increased in slow waves, while fast waves played more important roles in the global brain network and in the centrality of the local network,especially in theforehead duringIS ictal onset(P＜0.05). The alpha band was stronger in the global and local network during the waking time(P＜0.05). Conclusion: The overconnectivityof fast wave,the high local connectivity and defense capability of slow wavemay reflect the pathogenesis of IS, while the alpha band played the most important role in the local and global network during the waking time.